2007
DOI: 10.1007/s11661-007-9289-0
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Interface Reactions between Silver and 95.5Sn-3.9Ag-0.6Cu and 63Sn-37Pb Solders

Abstract: The microstructure and rate kinetics were investigated for solid-state intermetallic compound (IMC) layer growth in Sn-Ag-Cu/Ag and Sn-Pb/Ag couples. The aging temperatures were 55°C to 205°C and 70°C to 170°C, respectively. The aging times were 1 day to 400 days. The SnAg-Cu/Ag IMC layer included the phases: Ag 3 Sn (dominant), the f phase, and a solid-solution phase, xAg-ySn, (94 to 96 at. pct Ag). Void formation was observed at the solder/IMC (Ag 3 Sn) interface, which was attributed to the Kirkendall effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Also the Kirkendall vacancy zone forms inside the tin layer instead of the underlying copper substrate [9]. There is no exact research yet about the effect of silver underlayers, although experiments of [27] show similar results about the interdiffusion of Ag and Sn, but in this research no evidence was found for the Sn-Ag intermetallics formation (Fig. 5c).…”
Section: Resultsmentioning
confidence: 54%
“…Also the Kirkendall vacancy zone forms inside the tin layer instead of the underlying copper substrate [9]. There is no exact research yet about the effect of silver underlayers, although experiments of [27] show similar results about the interdiffusion of Ag and Sn, but in this research no evidence was found for the Sn-Ag intermetallics formation (Fig. 5c).…”
Section: Resultsmentioning
confidence: 54%
“…These illustrated that the size of the solder joint has a significant impact on the diffusion behavior of metal elements in solder joints. However, the diffusion dynamics equation (x=x0+Dt ) was valid to calculate the thickness of the IMC layer in many research studies about the IMC layer growth, bonding pad depletion and electromigration (Wu et al , 2009; Choi et al ., 2003; Kim et al , 2008; Vianco et al , 2007; Lee et al , 2003; Chang and Chiang, 2004; Jeon et al , 2003). On the macroscopic scale, the concentration of metal elements which diffuse into the solder layer is lower and exhibits little change during aging.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Furthermore, the minor species in solder can also affect the growth of interfacial IMCs. [13][14][15][16][17][18][19][20][21] For instance, a small amount of Ni in solder is able to influence the growth of microstructure in the Cu 6 Sn 5 IMCs. [22][23][24][25] It is reported that the addition of Ni atoms will ease the formation of Cu 3 Sn.…”
mentioning
confidence: 99%